Lumican as a potential biomarker for diabetic nephropathy - Yuejia Tao; Yipeng Liu; Zunsong Wang; Lijun Tang; Ying Zhang; Shanshan Zheng; Ruixue Wang; Kai Wei; Shunyao Liu (Renal Failure)
Objective We employed bioinformatics to identify potential biomarkers for diabetic nephropathy (DN) and investigate the role of the key gene lumican in its molecular processes.Methods We analyzed the GSE96804 and GSE30528 DN datasets from the Gene Expression Omnibus (GEO). GO and GSEA–KEGG enrichment analyses were used to identify key biological functions and related pathways. Cytoscape software was used to screen differentially expressed genes (DEGs) to obtain hub genes. The Nephroseq database was used to analyze the effect of hub genes on renal function, and the importance of lumican, a gene potentially related to DN progression, was further examined in clinical samples. GO and KEGG analyses were performed on lumican and its interacting proteins to elucidate their main biological functions and related pathways.Results We identified 1139 DEGs. GO enrichment analysis revealed that the DEGs were mainly involved in responses to hexose, cell–cell junctions. GSEA–KEGG enrichment analysis indicated that the DEGs were related to amino acid metabolism, adipokine signaling. Nephroseq database analysis revealed that hub genes were upregulated in the kidney tissues of patients with DN and that their expression was negatively correlated with estimated glomerular filtration rate (eGFR). Lumican was among the top hub genes, and its expression was increased in renal tissues of DN patients as confirmed by immunohistochemistry and immunofluorescence. GO and KEGG enrichment analyses revealed that lumican and its interacting proteins were associated with extracellular matrix organization.Conclusion Lumican is a potential biomarker for predicting DN and is closely related to the extracellular matrix. These findings provide novel insights into the clinical diagnosis and treatment of DN.